Body‐worn cameras offer multiple benefits. Issue 12 (April 2017) - Hope, Joan
Abstract : If an encounter with police or security officers gets tense, chances are someone will pull out a cell phone and take a video. Sometimes that footage can be shown out of context, so officers having footage of their own can be a real benefit.